Graphene / nano SiO synergistically enhanced self-repairing waterproof coating and preparation method thereof

The self-healing waterproof coating, enhanced by graphene/nano-SiO2 synergy, solves the problems of weather resistance, interfacial adhesion, freeze-thaw resistance, self-healing and environmental adaptability of existing waterproof coatings, and realizes a high-performance roof waterproof coating suitable for different climates and construction conditions.

CN121471739APending Publication Date: 2026-02-06SHENZHEN ZHUTUJIA BUILDING MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511887704.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-15
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

Existing two-component cement-based polymer waterproof coatings for exposed roofs have problems such as poor weather resistance, weak interface adhesion, easy damage from freeze-thaw cycles, lack of self-healing mechanism, poor adaptability to acid and alkali environments, easy cracking at low temperatures, low solids content, and environmental unfriendliness, which cannot meet the requirement of a 30-year exposed design life.

Method used

The self-healing waterproof coating is enhanced by the synergistic effect of graphene/nano-SiO2. It adopts a two-component system design, in which component A is responsible for flexibility and self-healing, and component B is responsible for early strength and continuous densification. The mass ratio of A to B is 1:1.2. When mixing on site, 0-5% water is added and the coating is cured at room temperature to form a film. The performance is improved by the synergistic dispersion of graphene oxide/nano-SiO2 and functional additives.

Benefits of technology

It achieves double the weather resistance life of the coating, reliable interface adhesion, continuous strength growth, self-healing cracks, and adaptability to all environments, meeting the weather resistance and waterproof performance requirements of a 30-year exposed design life, and is suitable for all seasons in the north and south and different construction environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121471739A_ABST
    Figure CN121471739A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene / nano SiO2 synergistically enhanced self-repairing waterproof coating and a preparation method thereof, and belongs to the technical field of waterproof coatings and the technical field of building waterproof materials. The coating comprises a component A (liquid) and a component B (powder), wherein the mass ratio of the component A to the component B is 1: 1.2; the component A is composed of a high-weather-resistance emulsion, a graphene oxide / nano SiO2 synergistic dispersion and a functional aid, and the component B is composed of sulphoaluminate cement, high belite sulfate cement, high-alumina fly ash microspheres and a plurality of functional powders. Through the four-in-one design of the high-weather-resistance fluorosilicone-styrene-acrylic compound emulsion, GO (at) SiO2 interface bridging, sulphoaluminate-high belite continuous hydration and LDH-nano CaO reversible minerals, the seven major pain points that an existing waterproof coating is short in weather resistance, poor in interface, weak in freeze thawing, free of self-healing, acid-base brittleness, low-temperature cracking and not environmentally friendly are solved; the technical effects of 30-year exposure and weather resistance, 72-hour self-repairing efficiency greater than or equal to 95%, no crack at-20 DEG C and VOC less than or equal to 50g / L are achieved, and the waterproof coating is suitable for roof exposure waterproof engineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of waterproof coating technology, and in particular to a self-healing waterproof coating enhanced by graphene / nano-SiO2 synergy and its preparation method. Background Technology

[0002] Currently, two-component cement-based polymer waterproof coatings for exposed roofs are the mainstream product in the industry. Their system consists of a liquid component (component A) and a powder component (component B): component A uses styrene-acrylic or pure acrylic emulsion as the sole organic phase, supplemented with defoamers, film-forming aids, and inert fillers such as heavy calcium carbonate / talc; component B is mainly composed of ordinary silicate cement and continuously graded quartz sand, mixed with redispersible latex powder, polycarboxylate superplasticizer, etc., and some formulations add fibers to improve crack resistance. This type of coating provides early strength through the formation of CSH gel by cement hydration, and the polymer film forms an interpenetrating network of "flexible continuous phase + rigid cement phase" to achieve adhesion, flexural strength, and impermeability.

[0003] However, existing technologies have many core defects: 1) Styrene-acrylic / pure acrylic emulsions have poor UV resistance and hydrolysis resistance. After 500 hours of xenon lamp aging, the tensile strength retention rate is less than 60%, and it will powder and crack in 2-3 years; 2) The inert filler and organic phase are only physically anchored. After long-term immersion in water, the interface hydrolyzes, and the peel strength decreases by more than 40%; 3) After the cement is hydrated once, there is no subsequent densification. After 150 freeze-thaw cycles, it will peel and the strength will shrink; 4) The coating has no self-healing mechanism after cracking and requires manual repair; 5) It lacks bidirectional adaptability to acid rain (pH 3-5) and alkaline substrates (pH > 12), and is prone to "efflorescence-blistering" failure; 6) It will break when bent at -20℃, and is prone to cracking during spring construction in northern regions; 7) The solid content is low (A:B=1:3), resulting in high packaging and transportation costs, and the VOC content is 80-120g / L, making it difficult to meet the Class A standard for green building materials.

[0004] The aforementioned defects result in existing roof waterproofing coatings having common industry problems such as "short weather resistance, poor interface, weak freeze-thaw resistance, lack of self-healing, acid and alkali brittleness, low-temperature cracking, and lack of environmental protection," which cannot meet the 30-year exposed design life requirement of building waterproofing. Summary of the Invention

[0005] This invention aims to address the seven core pain points of existing two-component cement-based polymer waterproof coatings, and provides a graphene / nano-SiO2 synergistically enhanced self-healing waterproof coating and its preparation method, achieving the full-function goals of "30-year weather resistance under exposure, long-term interfacial adhesion, continuous strength growth, self-healing of cracks, acid and alkali low-temperature compatibility, and green and low-consumption".

[0006] Technical solution: To solve the above-mentioned technical problems, according to one aspect of the present invention, more specifically, the present invention adopts a two-component system, wherein component A (liquid) is responsible for "flexibility, weather resistance, and self-healing triggering", and component B (powder) is responsible for "early strength, continuous densification, and mineral healing". The mass ratio of A to B is 1:1.2. 0-5% water is added during on-site mixing, and the mixture is cured into a film at room temperature.

[0007] (I) Composition and preparation of component A (liquid) Component A, by mass parts, includes the following components: High weather-resistant emulsion: 45-55 parts, compounded from fluorinated acrylate-organosilicon core-shell emulsion and carbon-carbon double bond styrene-acrylate emulsion at a dry mass ratio of (0.2-1):1; wherein the fluorinated acrylate-organosilicon core-shell emulsion has a core Tg of -25~-15℃, a shell Tg of 25~40℃, a fluorine content of 0.8-1.5%, and a solid content of 50-55%; the carbon-carbon double bond styrene-acrylate emulsion has a Tg of -10~0℃, a solid content of 55-58%, an acid value of 15-25mgKOH / g, and an iodine value ≤0.5%.

[0008] Graphene oxide / nano SiO2 synergistic dispersion (20% solid content): 11-18 parts. Preparation steps: Heat 5 mg / mL GO aqueous dispersion to 50±2℃; add 30% nano SiO2 sol (particle size 10-20 nm), GO:SiO2 dry mass ratio is 1:3; sonicate + shear at 3000 rpm for 30 min; add 0.5-1 parts KH-570 + 0.3-0.6 parts lanthanum isooctanoate titanate, continue shearing for 15 min; cool to 25℃ to obtain GO@SiO2 binary sheet dispersion with Zeta≤-45mV and average particle size of 120 nm.

[0009] Functional additives: 0.2-2 parts, including film-forming aids (one or a combination of dodecyl alcohol ester, dipropylene glycol butyl ether, and propylene glycol phenyl ether), thickeners (one of polyurethane associative type, alkali-swellable type, and hydroxyethyl cellulose), defoamers (mineral oils / organosilicones), and bactericides (MIT / BIT compound).

[0010] Preparation method of component A: Add the high weather-resistant emulsion to the stirring tank, add the graphene oxide / nano SiO2 synergistic dispersion under low speed (300 rpm), and stir for 15 min; then add various functional additives in sequence, and continue stirring for 20 min to obtain a uniform component A liquid.

[0011] (II) Composition and preparation of component B (powder) Component B, by mass parts, includes the following components: Sulfoaluminate cement (CSA52.5): 40-50 parts; High belite sulfate cement (HBC): 15-20 parts; High-alumina fly ash microspheres (average 3μm): 10-15 parts; Anhydrous gypsum (CaSO4): 3-5 parts; 2-3 parts of silica-alumina-calcium microcrystalline filaments (diameter ≤5μm, aspect ratio 30-50); Hydrotalcite (Mg-AlLDH, interlayer CO3) 2 (⁻): 3-5 portions; Nano CaO (50nm, stearic acid surface modified): 2-3 parts; Early-strength, slow-setting compound salt (calcium formate: sodium citrate = 2:1): 0.3-0.5 parts; Superdispersed polycarboxylate superplasticizer: 0.2-0.4 parts.

[0012] Preparation method of component B: Add the above powder raw materials to a dry powder mixer in proportion, mix at high speed (1500 rpm) for 30 min, and pass through a 200-mesh sieve to obtain uniform component B powder.

[0013] (III) Construction and preparation steps of waterproof coating Surface preparation: Remove dust and oil stains from the surface. If cracks in the old roof are greater than 1cm, inject epoxy resin to level the surface and ensure that the moisture content of the surface is ≤10%. Ingredient mixing: Take the ingredients according to the mass ratio of A:B=1:1.2, add 0-5% water, stir with an electric mixer (450rpm) for 2 minutes, and let stand for 3 minutes to defoam; Coating application: Can be applied by roller or spray. When roller coating, apply two cross-coats with a 6-hour interval, for a total wet thickness of 1.8-2.0 mm (dry film thickness of 1.2-1.5 mm). When spraying, use an airless sprayer with a pressure of 0.4-0.6 MPa and a gun distance of 30-40 cm. One coat will form a thickness of 1.2 mm, and can be re-sprayed to a thickness of 1.5 mm. Curing: Under conditions of 5-35℃ and RH≥50%, it can be exposed after natural curing for 24 hours. Avoid water accumulation within 3 days. It will reach 80% of its final strength in 7 days and complete secondary hydration / carbonization in 28 days.

[0014] The beneficial effects of the graphene / nano-SiO2 synergistically enhanced self-healing waterproof coating and its preparation method of the present invention are as follows: Increased weather resistance and lifespan: Fluorosilicone-styrene-acrylic composite emulsion combined with graphene oxide UV shielding layer, tensile strength retention rate of xenon lamp ≥90% after 1000h, meeting the requirement of 30 years of exposure without repair. Reliable bonding at the interface: The GO@SiO2 binary sheets bridge the organic and inorganic phases through chemical bonds, and the peel strength remains ≥95% after immersion in water for 168 hours, preventing peel leakage; Strength continues to increase: The combination of sulfoaluminate-high belite double cement and nano-SiO2 secondary pozzolanic reaction results in a strength increase of ≥10% after 200 freeze-thaw cycles, achieving "the more you use, the stronger it becomes"; Highly efficient self-healing of cracks: The LDH-nano CaO reversible mineral system combined with the GO photothermal effect can achieve a self-repair efficiency of ≥95% for 0.5mm cracks within 72 hours, turning "post-event repair" into "in-process self-healing". All-environment adaptability: It can resist acid rain and alkaline base corrosion, and can be bent at a low temperature of -20℃ without cracking. It is suitable for all seasons in the north and south and all scenarios with alternating dry and wet conditions. Attached Figure Description

[0015] The present invention will now be described in further detail with reference to the accompanying drawings and specific implementation methods.

[0016] Figure 1 This is a process flow diagram of the present invention. Detailed Implementation

[0017] The present invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and features described in the present application can be combined with each other.

[0018] To make the technical solution of the present invention clearer, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.

[0019] Example 1 Reference Figure 1 The self-healing waterproof coating synergistically enhanced by graphene / nano-SiO2 and its preparation method are as follows: (I) Preparation of Component A By mass fraction, take 20 parts of fluorinated acrylate-organosilicon core-shell emulsion (core Tg=-20℃, shell Tg=30℃, fluorine content 1.2%, solid content 52%) and 30 parts of carbon-carbon double bond styrene-acrylate emulsion (Tg=-5℃, solid content 56%, acid value 20mgKOH / g), and mix them to obtain a high weather-resistant emulsion; take 15 parts of graphene oxide / nano SiO2 synergistic dispersion (solid content 20%); take 1 part of film-forming aid dodecyl alcohol ester, 0.5 parts of thickener polyurethane associative type, 0.3 parts of defoamer organosilicon, and 0.2 parts of bactericide MIT / BIT compound.

[0020] Add the high weather-resistant emulsion to a stirred tank, add the graphene oxide / nano SiO2 synergistic dispersion under low-speed stirring at 300 rpm, and stir for 15 min; then add the functional additives in sequence, and continue stirring for 20 min to obtain component A.

[0021] (II) Preparation of Component B By weight, take 45 parts of sulfoaluminate cement (CSA52.5), 18 parts of high belite sulfate cement (HBC), 12 parts of high-alumina fly ash microspheres, 4 parts of anhydrous gypsum, 2.5 parts of silica-alumina-calcium microcrystalline filaments, 4 parts of hydrotalcite, 2.5 parts of nano-CaO (50nm, stearic acid modified), 0.4 parts of early-strength-retarding composite salt, and 0.3 parts of polycarboxylate superplasticizer.

[0022] The above powder was added to a dry powder mixer and mixed at 1500 rpm for 30 minutes. The mixture was then passed through a 200-mesh sieve to obtain component B.

[0023] (III) Preparation and Application of Waterproof Coatings Mix A:B at a mass ratio of 1:1.2, add 3% water, stir at 450 rpm for 2 minutes, let stand for 3 minutes to defoam, apply two cross-coats by roller coating, with a total wet thickness of 1.9 mm, cure at 25℃ and RH 60% for 24 hours, and test performance after 7 days.

[0024] Conclusion: This embodiment employs a moderate ratio of high weather-resistant emulsion and functional powder, with a suitable blending ratio of fluorosilicone core-shell emulsion and styrene-acrylic emulsion. The GO@SiO2 dispersion is added in 15 parts, and the sulfoaluminate cement and high-belite sulfate cement are balanced in the dual-cement system, balancing the flexibility and rigidity of the coating. Adding 3% water during construction provides good leveling and spreadability, and the 25°C room temperature curing condition suits the construction environment in most regions. The final waterproof coating meets all the core technical indicators of this invention, exhibiting excellent weather resistance, self-healing ability, and interfacial adhesion. This is the preferred embodiment of this invention and is suitable for most conventional construction scenarios in exposed roof waterproofing projects.

[0025] Example 2 Reference Figure 1 The self-healing waterproof coating synergistically enhanced by graphene / nano-SiO2 and its preparation method are as follows: (I) Preparation of Component A By mass, 15 parts of fluorinated acrylate-organosilicon core-shell emulsion (core Tg=-25℃, shell Tg=25℃, fluorine content 0.8%, solid content 50%) and 35 parts of carbon-carbon double bond styrene-acrylate emulsion (Tg=-10℃, solid content 55%, acid value 15mgKOH / g) were mixed to obtain a high weather-resistant emulsion; 11 parts of graphene oxide / nano SiO2 synergistic dispersion were taken; 0.8 parts of film-forming aid dipropylene glycol butyl ether, 0.4 parts of thickener alkali-swellable type, 0.4 parts of defoamer mineral oil, and 0.3 parts of bactericide MIT / BIT compound were taken.

[0026] The preparation process was the same as in Example 1, and component A was obtained.

[0027] (II) Preparation of Component B By weight, take 40 parts of sulfoaluminate cement, 15 parts of high belite sulfate cement, 10 parts of high-alumina fly ash microspheres, 3 parts of anhydrous gypsum, 2 parts of silica-alumina-calcium microcrystalline filaments, 3 parts of hydrotalcite, 2 parts of nano-CaO, 0.3 parts of early-strength-retarding composite salt, and 0.2 parts of polycarboxylate superplasticizer.

[0028] The preparation process was the same as in Example 1, and component B was obtained.

[0029] (III) Preparation and Application of Waterproof Coatings Mix A:B at a mass ratio of 1:1.2, add 0% water, stir at 450 rpm for 2 minutes, and let stand for 3 minutes to defoam. Use airless spraying at a pressure of 0.5 MPa and a gun distance of 35 cm to form a 1.2 mm layer in one pass. Cure at 10℃ and RH 50% for 24 hours and test performance after 7 days.

[0030] Conclusion: This embodiment uses low-ratio functional components and powder raw materials, reducing the amount of GO@SiO2 dispersion to 11 parts. The addition amounts of double cement and various functional powders are also the lowest in this embodiment. Furthermore, no additional water was added during construction, resulting in a higher overall solids content in the coating. The 10℃ low-temperature curing condition simulates the construction environment in northern spring, and the airless spraying method is suitable for the rapid construction needs of large-area roofs. The waterproof coating prepared in this embodiment significantly reduces raw material costs while ensuring core performance standards are met. It also exhibits low-temperature construction adaptability, making it suitable for large-area roof waterproofing projects in cold northern regions. This demonstrates the flexibility of this invention in terms of raw material ratios and construction scenarios.

[0031] Example 3 Reference Figure 1 The self-healing waterproof coating synergistically enhanced by graphene / nano-SiO2 and its preparation method are as follows: (I) Preparation of Component A By mass fraction, 25 parts of fluorinated acrylate-organosilicon core-shell emulsion (core Tg=-15℃, shell Tg=40℃, fluorine content 1.5%, solid content 55%) and 25 parts of carbon-carbon double bond styrene-acrylate emulsion (Tg=0℃, solid content 58%, acid value 25mgKOH / g) were mixed to obtain a high weather-resistant emulsion; 18 parts of graphene oxide / nano SiO2 synergistic dispersion were taken; 1.2 parts of film-forming aid propylene glycol phenyl ether, 0.6 parts of thickener hydroxyethyl cellulose, 0.5 parts of defoamer organosilicon, and 0.4 parts of bactericide MIT / BIT compound were taken.

[0032] The preparation process was the same as in Example 1, and component A was obtained.

[0033] (II) Preparation of Component B By weight, take 50 parts of sulfoaluminate cement, 20 parts of high belite sulfate cement, 15 parts of high-alumina fly ash microspheres, 5 parts of anhydrous gypsum, 3 parts of silica-alumina-calcium microcrystalline filaments, 5 parts of hydrotalcite, 3 parts of nano-CaO, 0.5 parts of early-strength-retarding composite salt, and 0.4 parts of polycarboxylate superplasticizer.

[0034] The preparation process was the same as in Example 1, and component B was obtained.

[0035] (III) Preparation and Application of Waterproof Coatings Mix A:B at a mass ratio of 1:1.2, add 5% water, stir at 450 rpm for 2 minutes, let stand for 3 minutes to defoam; apply by roller coating to a total wet thickness of 2.0 mm, cure at 35℃ and 70% RH for 24 hours, and test performance after 7 days.

[0036] Conclusion: This embodiment utilizes a high proportion of functional components. The fluorine and solids content of the fluorosilicone core-shell emulsion are the highest, the GO@SiO2 dispersion is added at 18 parts, and the addition amounts of double cementitious materials, hydrotalcite, and nano-CaO functional powders are also at their maximum. During construction, 5% water is added, and the coating thickness reaches 2.0 mm. The high-temperature and high-humidity curing conditions at 35℃ simulate the environment of hot and humid southern regions. The waterproof coating prepared in this embodiment exhibits optimal performance in terms of weather resistance, self-healing efficiency, and strength gain. It is particularly suitable for exposed roof projects in hot and humid southern regions with frequent acid rain or extremely high waterproofing requirements. This verifies that the present invention can achieve superior performance gains with a high proportion, meeting the needs of high-end waterproofing projects. The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A graphene / nano-SiO2 synergistically reinforced self-repairing waterproof coating, characterized in that, It comprises A component (liquid material) and B component (powder material), the mass ratio of A:B is 1:1.2; the A component comprises, in parts by mass: high weatherability emulsion 45-55 parts, graphene oxide / nano-SiO2 synergistic dispersion 11-18 parts, functional additives 0.2-2 parts; the high weatherability emulsion is compounded by fluorine-containing acrylate-silicone core-shell emulsion and carbon-carbon double bond-containing styrene-acrylate emulsion at a dry mass ratio (0.2-1):1; the graphene oxide / nano-SiO2 synergistic dispersion is GO@SiO2 binary sheet dispersion with Zeta≤-45 mV and average particle size 120 nm; the B component comprises, in parts by mass: sulphoaluminate cement (CSA52.5) 40-50 parts, high belite sulphate cement (HBC) 15-20 parts, high-aluminum fly ash microbead 10-15 parts, anhydrous gypsum 3-5 parts, silicon-aluminum-calcium microcrystalline filament 2-3 parts, hydrotalcite 3-5 parts, nano-CaO 2-3 parts, early strength-retarding composite salt 0.3-0.5 parts, and super-dispersed polycarboxylic acid water reducer 0.2-0.4 parts. 2.The graphene / nano-SiO2 synergistically reinforced self-repairing waterproof coating according to claim 1, characterized in that, The core Tg of the fluorine-containing acrylate-silicone core-shell emulsion is -25~-15℃, the shell Tg is 25~40℃, the fluorine content is 0.8-1.5%, and the solid content is 50-55%; the Tg of the carbon-carbon double bond-containing styrene-acrylate emulsion is -10~0℃, the solid content is 55-58%, the acid value is 15-25 mgKOH / g, and the iodine value is ≤0.5%. 3.The graphene / nano-SiO2 synergistically reinforced self-repairing waterproof coating according to claim 1, characterized in that, The preparation steps of the graphene oxide / nano-SiO2 synergistic dispersion are: heating 5mg / mL GO water dispersion to 50±2℃; adding 30% nano-SiO2 sol, the dry mass ratio of GO:SiO2 is 1:3; ultrasonic + 3000rpm shearing for 30min; adding KH-570 0.5-1 parts + lanthanum-isooctanoate titanate 0.3-0.6 parts, continuing shearing for 15min; cooling to 25℃, to obtain the dispersion; the particle size of the nano-SiO2 sol is 10-20nm. 4.The graphene / nano-SiO2 synergistically reinforced self-repairing waterproof coating of claim 1, characterized in that, The functional additives in the A component include film-forming aids, thickening agents, defoaming agents, and bactericides; the film-forming aids are one or a combination of dodecanol ester, dipropylene glycol butyl ether, and propylene glycol phenyl ether; the thickening agent is one of polyurethane association type, alkali-swellable type, and hydroxyethyl cellulose; the defoaming agent is mineral oil or silicone; and the bactericide is MIT / BIT compound. 5.The graphene / nano-SiO2 synergistically reinforced self-healing waterproof coating of claim 1, characterized in that, The nano-CaO in the B component is 50nm in particle size and is surface-modified by stearic acid; the early strength-retarding composite salt is compounded by calcium formate and sodium citrate at a mass ratio of 2:1; the silicon-aluminum-calcium microcrystalline filament is ≤5μm in diameter and has a length-diameter ratio of 30-50; and the high-aluminum fly ash microbead is 3μm in average particle size.

6. The preparation method of graphene / nano-SiO2 synergistically reinforced self-repairing waterproof coating, characterized in that, It comprises the following steps: (1) A component preparation: adding high weatherability emulsion into a stirred tank, adding graphene oxide / nano-SiO2 synergistic dispersion under low-speed stirring, stirring for 15min; then adding functional additives in sequence, continuing stirring for 20min, to obtain the A component; (2) Preparation of B component: Add sulphoaluminate cement, high belite sulphate cement, high-alumina fly ash microsphere, anhydrous gypsum, silica-alumina calcium microcrystalline silk, hydrotalcite, nano CaO, early strength-retarder composite salt, polycarboxylic acid water reducer into a dry powder mixer according to the proportion, mix at high speed for 30 min, pass through a 200-mesh sieve, and obtain B component; (3) Preparation of waterproof coating: Take A component and B component according to the mass ratio of A:B = 1:1.2, add 0-5% water, stir at 450 rpm for 2 min, stand for 3 min to defoam, and obtain the waterproof coating.

7. The preparation method of graphene / nano-SiO2 synergistically reinforced self-repairing waterproof coating according to claim 6, characterized in that, The rotation speed of low-speed stirring in step (1) is 300 rpm; and the rotation speed of high-speed mixing in step (2) is 1500 rpm.

8. The preparation method of graphene / nano-SiO2 synergistically reinforced self-repairing waterproof coating according to claim 6, characterized in that, The construction steps of the waterproof coating also include: Base surface treatment: remove floating dust and oil stains on the base surface, fill epoxy glue to level when the crack of the old roof is greater than 1 cm, and ensure that the water content of the base surface is less than or equal to 10%; Coating construction: use rolling or spraying to coat, cross two times when rolling, with an interval of 6 h, and the total wet thickness is 1.8-2.0 mm; when spraying, the pressure of airless sprayer is 0.4-0.6 MPa, the gun distance is 30-40 cm, and the thickness of one pass is 1.2 mm; Curing: naturally cure at 5-35℃ and RH≥50% for 24 h, avoid water accumulation within 3 d, reach 80% of the final strength after 7 d, and complete secondary hydration / carbonization after 28 d.